Hotel industry growth trends –the case of intercontinental hotels group - Avelar, Pedro Alexandre Santos (2020)
IHG is considered one of the biggest companies fromhotelindustry.Its presence is spread worldwide, accounting with more than 5,600 franchised, managed, owned and leased hotels. Its revenues are reported according to three regions –Americas, EMEAA and Greater China.IHG has been developingexpansionist strategies, improving its business models and aligningits corporate goalsin order to obtain long-term sustainability. We performedananalysis of IHG business modelsandvalue drivers, researched about its majorcompetitors andincorporated the mainindustry trendsin the forecast.It was adopted the DCFmethodology in order to determine the FY20 share price.